Experimental comparison at open and closed vertical multidecks display cases at standard and tropical environmental conditions - Heidinger, Gustavo Galdi (2018)
This paper reports the results of experimental tests performed according to ISO 23953 in vertical open and closed multideck display cases to evaluate the influence of double glass doors in the direct energy consumption, product simulator temperature, evaporator total condensed water mass, total heat load and total energy consumption. Tests were performed at climate classes n.º 3 (Ta = 25°C; a = 60%) and n.º 6 (Ta = 27°C; a = 70%). The direct energy consumption is 46% higher at the closed display case due to the heat load generated by the heated glass doors frame and defrost heaters. The product simulator temperature is higher and more stable at the open display case. The highest product simulator temperature is lower (-1.4°C) at the closed display case and less stable (+2.7°C variation) due to the opening doors period. The total mass of condensed water at the evaporator is reduced 87% and the total energy consumption is 58% lower at the closed display case. In conclusion, the estimated total energy consumption (compressor and components) is reduced at the glass doors display case. Thus, it is verified that the use of refrigeration equipment closed to ambient air is increasingly seen as the definitive solution, given the current concerns with energy consumption and sustainability of the heat exchange processes.